A new species of Procontarinia (Diptera: Cecidomyiidae) damaging fruit of mango, Mangifera indica (Anacardiaceae), in China - Jiao, Ke-Long; Wang, Hao; Wei, De-Wei; Mo, Jian-You; Wang, Yuan-Hong; Bu, Wen-Jun; Kolesik, Peter (Zootaxa, 2018)
Larvae of a previously unknown species of gall midge were found feeding on young fruit of mango, Mangifera indica (Anacardiaceae), in Guangxi Autonomous Region in southern China, causing severe damage to the crop. The new species is named Procontarinia fructiculi Jiao, Wang, Bu & Kolesik, its morphology is described, the basic biology is given, and the Cytochrome Oxidase subunit I (COI) mitochondrial gene segment is sequenced and compared to other congeners. Procontarinia contains now 16 described species, each feeding on mango. All but three species cause variously shaped galls on leaves, while P. mangiferae (Felt) malforms inflorescence and young leaves, and two species feed on fruit – P. frugivora Gagné causing deep lesions and P. fructiculi sp. nov. tunnel-like holes. Of the two fruit-feeding species, P. frugivora is confined to the Philippines while the new species has thus far been recorded only from southern China.